Hyaline Protoplasmic Astrocytopathy in the Setting of Epilepsy: A Literature Review and Report of 2 Cases. Issue 2 (10th December 2022) - Alzoubi, Hiba; Nobile, Giulia; d'Amati, Antonio; Nobili, Lino; Giacomini, Thea; Tortora, Domenico; Gaggero, Gabriele; Gianno, Francesca; Giangaspero, Felice; Antonelli, Manila; Consales, Alessandro
Abstract: Objectives: Cerebral hyaline protoplasmic astrocytopathy (HPA) is a clinicopathologic entity characterized by eosinophilic cytoplasmic inclusions within astrocytes. It has been observed in a subset of patients with early-onset epilepsy, brain malformations, and developmental delay. The exact association of this entity with epilepsy is still unknown. This report, with its review of the literature, aims to summarize HPA features to raise awareness regarding this entity. Methods: We report on 2 HPA cases and critically review the literature. Results: Approximately 42 cases of HPA have been reported, including the 2 cases presented here, consisting of 23 female and 19 male patients. Patient age ranged from 3 to 39 years. All patients had early-onset seizures (3-20 months of age), ranging from partial to generalized, that were refractory despite treatment with antiepileptic drugs. Postoperative follow-up intervals ranged from 2 to 93 months, and the clinical outcome was graded according to the Engel classification, showing variable results. Conclusions: Clinicians should consider HPA in differential diagnosis in patients with intractable seizures, especially when they are associated with developmental delay and brain malformations. Increasing awareness of this entity among pathologists may promote better understanding of this condition as well as better diagnosis and treatment for these patients.